Theologies, wings and cages: welcoming the challenges of diversity, so as not to hide the theologies - Méndez, José Mario (Teoría y Praxis, 2022)
Theologies, wings and cages: welcoming the challenges of diversity, so as not to hide the theologies, N° 35, january-july 2019